Caregivers’ anxiety and perception of their children’s wellbeing: a year into the COVID-19 pandemic - Pena-Shaff, Judith; Heckart, Ashtyn; Mannion, Caroline; Barry, Kayla (Frontiers in Psychology, 2023)
The COVID-19 pandemic and related social restrictions disrupted family routines affecting millions of youths and their caregivers worldwide. This study explored the relationship between caregivers’ anxiety and their children’s emotional states 1 year after COVID-19, as well as differences between caregivers’ perceptions of their children’s emotional states and reality. Sixty-eight caregiver-child pairs completed an online survey between March 31 and May 31, 2021. Our analysis showed positive correlations between caregivers’ anxiety and children’s wellbeing, worries about children’s use of time, and a variety of negative emotional states in their children. Caregivers’ anxiety about their children’s wellbeing was negatively correlated with their children’s perceptions of self-control. Caregivers’ anxiety about their personal wellbeing was negatively correlated with children’s feelings of busyness and positively associated to their children’s fear. Caregivers’ perception of COVID-19 as a challenging experience was positively associated with some of their children’s negative emotions. Overall, caregivers were accurate about children’s emotional experiences in the previous 3 months with some exceptions: their children felt lonelier and more worried about schoolwork and grades than their caregivers realized. These findings will help researchers and practitioners further explore the sources of caregivers’ anxiety and their relationship with children’s emotions and stress management as countries move toward a new normal.